Increasing the Interests and Talents of Children in Titi Payung Village in Learning English and Malay - Dewi Sartika Br Ginting; Yurina Indah Silvia; Tampubolon, Yolanda Maritho; Farizkillah, Agis (Talenta Publisher, 2023)
Language is an essential thing that is applied in almost every field of life, including in the field of education, bussiness, industry, entertainment, etc. In the current era of globalization, English is very important to master because English is one of the most widely used international official languages ​​to communicate globally. Learning English opens various opportunities both in education and career of an individual. Children in Titi Payung Village, Batu Bara District, Air Putih District, Sumatra Utara Province have some difficulties in approaching and learning English. Besides English, of course, the local language also needs to be preserved in order to study and introduce culture to the outside world. The people in Titi Payung Village have a diverse ethnic backgrounds, including Javanese, Bataknese and Malay. By that the children in Titi Payung Village are the right target for learning Malay in order to conserve the Malay culture. Based on this, students from the Faculty of Cultural Sciences, University of North Sumatra took part in the KKNT-2022 activities and held programs of theaching languages such as English (English Course) and Malay to the children in Titi Payung Village namely in the Rumah Belajar program. This is done with the aim of improving language skills in children with carry out teaching English and Malay to children in Titi Payung Village and publish every activity to Titi Payung`s KKNT-36's social media account so that it is known and supported by the community.